Osseointegration Levels of Implants Placed With Allogenic and Xenogenic Bone Ring: An Experimental Biomechanical Analysis - Gul, Mehmet; Bozoglan, Alihan; Dundar, Serkan; Bingul, Muhammet Bahattin; Kirtay, Mustafa; Ozupek, Muhammet Fatih; Tasdemir, Ismail (Lippincott Williams & Wilkins, 2023)
This in vivo study aimed to do a biomechanical analysis of the early period bone-implant connection of titanium implants simultaneously inserted with xsenogenic and allogenic bone ring. In this study, 28 Sprague Dawley female rats were used. Four rats were killed to obtain an allogenic bone ring, and after this, the remaining rats were divided into control (n=8), xsenogenic (n=8), and allogenic (n=8) bone ring groups. Titanium-machined surfaced implants were integrated right tibias of the rats. In controls, only implants were integrated into right tibias. In the greft groups, the implants were integrated simultaneously with bone rings. After 2 weeks of the experimental period, the rats were killed ,and titanium implants and surrounding bone tissues were removed for biomechanic analysis. After biomechanical reverse torque analysis bone-implant connection was determined as Newton/cm(2); in controls 3.26 (1.2 to 4.5), in allogenic ring group 3.37 (2 to 4.4), in xsenogenic ring group 5.93 (2.8 to 10). Statistically significant differences were not detected between the groups (P>0.05). Within the limitation of this study, both allogenic and xsenogenic bone grafts could be successfully used in bone augmentation in implant surgery.
Keywords: Allogenic bone graft; xenogenic bone graft; bone ring; osseointegration; bone-implant connection; biomechanical analysis